Thermal limits of krill species from the high-Arctic Kongsfjord (Spitsbergen) - Hünerlage, Kim; Buchholz, Friedrich (Marine Ecology Progress Series, 2015)
The high-Arctic Kongsfjord is mainly influenced by cold Arctic water, but also receives input of warmer water from the Atlantic. In recent years, the proportion of Atlantic inflow from the south has increased. Concurrently, one temperate-boreal (Meganyctiphanes norvegica) and one subtropical-temperate (Nematoscelis megalops) krill species are now regularly found in the Kongsfjord, in addition to the previously prevailing arcto-boreal species Thysanoessa inermis and T. raschii. In light of the recent changes in these species’ biogeographic distributions, we compared their physiological tolerances. Using non-invasive optical oxygen sensors, respiration measurements served to characterize metabolic responses to temperature variations. The 2 Thysanoessa spp. appeared more cold-stenotherm than the other 2 krill species: the upper level of their respiratory capacity was reached at 12 degrees C and they were less tolerant of decreasing oxygen concentrations. This finding is consistent with their arcto-boreal distribution. In contrast, M. norvegica and N. megalops exhibited higher tolerance to temperature changes, robust nutritional condition and sexual maturity. Such physiological plasticity may explain the recent northward expansion of these species’ geographic range.